Extraordinary Measures in Extraordinary Times: Legal Response to the COVID-19 Crisis in Bosnia and Herzegovina - Milinković, Igor (Medicine, Law & Society, 2021)
The COVID-19 pandemic has profoundly affected all aspects of people’s daily lives. In response to the pandemic, many countries declared a state of emergency. Extraordinary measures have been implemented to reduce the spread of the new coronavirus. Some of these measures require significant restrictions of fundamental rights and freedoms, such as the right to privacy, freedom of movement, freedom of assembly, freedom of expression, religious freedoms etc. In Bosnia and Herzegovina (BiH), the BiH and entity authorities adopted decisions to provide a legal basis for implementation of extraordinary measures. The paper deals with the restrictive measures implemented during the COVID-19 crisis in BiH and their impact on human rights realization. The relevant decisions of the Constitutional Court of BiH are also analysed, including the decision in case AP-3683/20 according to which certain restrictive measures are contrary to the right to respect of private life and the freedom of movement.
Keywords: coronavirus pandemic, state of emergency, emergency situation, legal framework, human rights